Proof‐of‐Concept Study to Assess the Nociceptin Receptor Antagonist LY2940094 as a New Treatment for Alcohol Dependence. (20th July 2016) - Post, Anke; Smart, Trevor S.; Jackson, Kimberley; Mann, Joanne; Mohs, Richard; Rorick‐Kehn, Linda; Statnick, Michael; Anton, Raymond; O'Malley, Stephanie S.; Wong, Conrad J.
Abstract : Background: This was a proof‐of‐concept study to evaluate the efficacy of LY2940094, a nociceptin/orphanin FQ peptide receptor antagonist, in reducing alcohol consumption in actively alcohol‐drinking patients with alcohol dependence. Methods: Eighty‐eight patients, 21 to 66 years of age, diagnosed with alcohol dependence, reporting 3 to 6 heavy drinking days per week, were randomized (1:1) to 8 weeks of treatment with once‐daily oral placebo ( N  = 44) or 40 mg/d of LY2940094 ( N  = 44). The primary efficacy analysis was the change from baseline in number of drinks per day (NDD) utilizing mixed‐model repeated measures comparing LY2940094 and placebo in Month 2 of the 8‐week double‐blind treatment period. The probability that the difference relative to placebo in NDD was ≤0 at endpoint was calculated, and a probability ≥80% was considered to be evidence that LY2940094 was associated with the reduction in NDD. Results: After 8 weeks of treatment, reduction in mean NDD did not differ between LY2940094 versus placebo (−1.4 vs. −1.5, respectively, 44% probability of greater reduction relative to placebo), but there was a greater reduction in the mean percentage of heavy drinking days in a month with LY2940094 versus placebo (−24.5 vs. −15.7%, respectively, 93% probability of a greater reduction relative to placebo), and an increase in the mean percentage of abstinent days in a month compared to placebo (9.1 vs. 1.9%, respectively, 91% probability of a greater increase relative to placebo). Patients who were treated with LY2940094 showed decreased plasma levels of gamma‐glutamyl transferase with probabilities ≥98% for greater reduction compared with placebo at Weeks 1, 4, 6, and 8. Treatment‐emergent adverse events in ≥5% of patients treated with LY2940094 included insomnia, vomiting, and anxiety. There were no serious adverse events or significant changes in laboratory assessments or vital signs with LY2940094. Conclusions: Although not reducing the NDD, LY2940094, compared to placebo, did reduce heavy drinking days and increased abstinence days in patients with alcohol dependence. Abstract : This was a proof‐of‐concept study to evaluate the efficacy of LY2940094, a nociceptin/orphanin FQ peptide receptor antagonist, in reducing alcohol consumption in actively alcohol‐drinking patients with alcohol dependence. Although not reducing the number of drinks per day, LY2940094, compared to placebo, did reduce heavy drinking days and increased abstinence days in patients with alcohol dependence.